2021
DOI: 10.1101/2021.03.12.435168
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Individualized event structure drives individual differences in whole-brain functional connectivity

Abstract: Resting-state functional connectivity is typically calculated as a correlation between regional activity. It is studied widely, both to gain insight into the brain's intrinsic organization but also to develop markers sensitive to changes in an individual's cognitive, clinical, and developmental state. Despite this, the origins and drivers of functional connectivity, especially at the level of densely sampled individuals, remain elusive. Here, we leverage novel methodology to decompose functional connectivity i… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 17 publications
(37 citation statements)
references
References 109 publications
1
36
0
Order By: Relevance
“…S5). Interestingly, the spatial patterns of these clusters closely recapitulate those reported in previous studies [14,18]. Community 1, for instance, was characterized by opposed fluctuations between regions in the default mode network with those in dorsal and salience/ventral attention networks (Fig.…”
Section: Clustering High-amplitude Co-fluctuations Reveal Distinct Patterns Of Connectivitysupporting
confidence: 85%
See 1 more Smart Citation
“…S5). Interestingly, the spatial patterns of these clusters closely recapitulate those reported in previous studies [14,18]. Community 1, for instance, was characterized by opposed fluctuations between regions in the default mode network with those in dorsal and salience/ventral attention networks (Fig.…”
Section: Clustering High-amplitude Co-fluctuations Reveal Distinct Patterns Of Connectivitysupporting
confidence: 85%
“…Previous applications of edge time series analysis to functional imaging data have reported brief, intermittent, and high-amplitude "events" [14,[16][17][18]33]. These studies have shown that the co-fluctuation patterns expressed during events contribute disproportionately to the time-averaged pattern of FC, are subject-specific, can be clustered into a small number of putative "states", and strengthen brain-behavior associations.…”
Section: Discussionmentioning
confidence: 99%
“…In the previous section, we examined the presence of rapid and bursty fluctuations in ETS, highlighting this property as one of its main ways it differs from sw-tvFC. These high-amplitude fluctuations – referred to as “events” in previous papers [25] – are infrequent and, in previous work, were shown to be uncorrelated with in-scanner head motion [25, 26]. Therefore, they may be important in providing insights into the ongoing cognitive processes at rest and movie-watching conditions.…”
Section: Resultsmentioning
confidence: 91%
“…Previous studies have examined edge time series and characterized some of their basic properties [25, 26], speculating that these properties might serve as potent biomarkers for comparing individuals in terms of their cognitive or clinical states. However, with limited exceptions, these speculations have not been investigated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation